The Effect of Capital Structure, Accounting Conservatism, and Independent Commissioners on Earnings Quality with Company Size as a Moderation Variable - Andhita Saharani Azahra; Rina Mudjiyanti; Ani Kusbandiyah; Tiara Pandansari (Trescode Green Organization, 2024)
This research analyzed how capital structure, accounting conservatism, and independent commissioners influence earnings quality, with company size as a moderating factor. The study included 135 transportation and logistics sector companies from 2019 to 2023. The analysis method applied in this study was moderation regression analysis. The findings reveal that company size positively impacts earnings quality while accounting conservatism negatively influences earnings quality. In contrast, capital structure and independent commissioners do not affect earnings quality. Furthermore, company size enhances the impact of accounting conservatism on earnings quality, but it does not strengthen the effects of capital structure and independent commissioners on earnings quality. The findings imply that companies should carefully consider the role of accounting policies and organizational structure, particularly the moderation effect of company size, to improve the quality of reported earnings.